Peran Wali Kelas dalam Mengatasi Masalah Kesulitan Belajar Membaca Siswa Kelas III Di SDN 1 Bangkelekila’ - Yohanis Padallingan; Lita Yohanis (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The role of the homeroom teacher in overcoming the problem of learning difficulties of grade III students is very important because through its role the homeroom teacher can help students to overcome the problems difficulties the face. The difficulties faced by students also vary because students have different characteristics. This research aims to: (1) to find out the difficulties of students in the process of learning to read in grade III SDN 1 Bangkelekila’. (2) to find out the role of homeroom teacher in solving the problem of learning difficulties in reading for grade III to 1 students of Bangkelekila. The subject ini this research is the homeroom teacher og class III. This type of research is qualitative research with a case study research design. The informant of this research is the homeroom teacher. Data collection procedures used were observation, interviews, and documentation. Data analysis includes data reduction, data presentation, verification, checking the validity of the findings. The research stage includes the pre-field, stage the implementation stage, the data analysis stage the completion stage. The results of research in the field show that the role of the homeroom teacher in overcoming the problem of learning difficulties of grade III students is very important because through his role as a homeroom teacher can help the learning difficulties faced by students so that the sedifficulties can be cosolved properly and students can easily understand the lessons given by their teacher.